Tom of Finland [videorecording (DVD)] - Strang, Pekka, 1977-; Tilkanen, Lauri, 1987-; Grabowsky, Jessica, 1980- (Kino Lorber, 2018)
Dome Karukoski's stirring biopic Tom of Finland follows his life from the trenches of WWII and repressive Finnish society of the 1950s through his struggle to get his work published in California, where he and his art were finally embraced amid the sexual revolution of the 1970s. Tom's story is one of love, courage and perseverance, mirroring the gay liberation movement for which his leather-clad studs served as a defiant emblem.